The aorta can act as a site of naïve CD4+ T-cell priming. Issue 2 (13th April 2019) - MacRitchie, Neil; Grassia, Gianluca; Noonan, Jonathan; Cole, Jennifer E; Hughes, Catherine E; Schroeder, Juliane; Benson, Robert A; Cochain, Clement; Zernecke, Alma; Guzik, Tomasz J; Garside, Paul; Monaco, Claudia; et al.
Abstract: Aims: Aortic adaptive immunity plays a role in atherosclerosis; however, the precise mechanisms leading to T-cell activation in the arterial wall remain poorly understood. Methods and results: Here, we have identified naïve T cells in the aorta of wild-type and T-cell receptor transgenic mice and we demonstrate that naïve T cells can be primed directly in the vessel wall with both kinetics and frequency of T-cell activation found to be similar to splenic and lymphoid T cells. Aortic homing of naïve T cells is regulated at least in part by the P-selectin glycosylated ligand-1 receptor. In experimental atherosclerosis the aorta supports CD4+ T-cell activation selectively driving Th1 polarization. By contrast, secondary lymphoid organs display Treg expansion. Conclusion: Our results demonstrate that the aorta can support T-cell priming and that naïve T cells traffic between the circulation and vessel wall. These data underpin the paradigm that local priming of T cells specific for plaque antigens contributes to atherosclerosis progression.